Effect Of 'Janani Shishu Suraksha Karyakram' - A Government Health Beneficiary Scheme - On Admission Rate and Clinical Outcome in NICU in A Tertiary Care Hospital - Khyati M Kakkad; Megha S Patel; Snehal Patel; Pritesh (Medsci Publications, 2014)
Introduction: Neonatal deaths account for a major proportion of child deaths globally. Government of India has launched JSSK scheme on 1st June 2011 with an aim to reduced maternal mortality rate and infant mortality rate (MDG). Method: A retrospective observational study was carried out to know the effect of JSSK scheme on work load, availability of expensive treatment modality and effect on outcome. Study was carried out by comparing one year time period between SEP- 2011 to AUG 2012 (pre-JSSK year) and SEP-2012 to AUG-2013 (post-JSSK year, as it was implemented from Sept-2012 in the study hospital). Results: After JSSK scheme institutional deliveries increased by 20.32% and registered deliveries by 20.77%. NICU admission rate was increased by 21.96% with a significant increase in preterm admission by 86.89%. Use of expensive modern treatment modalities were increased by 3.97%. Neonatal death rate is reduced by 1.32% with significant decrease in preterm mortality by 12.99%. Most common causes of death in preterm in pre-JSSK period were septicaemia (41.76%), RDS (27.47%) and aspiration pneumonia (6.59%). While in post-JSSK period the most common causes were RDS (51.04%), sepsis (38.54%) and aspiration pneumonia (4.1%). Conclusion: JSSK is successful in raising the number of institutional deliveries, booked obstetric practice(hence a better antenatal care) and improved access to level III NICU care among the poor resulting in a significant decrease in preterm mortality rates.